2011
DOI: 10.1051/0004-6361/201015676
|View full text |Cite
|
Sign up to set email alerts
|

VLTI/AMBER spectro-interferometry of the Herbig Be star MWC 297 with spectral resolution 12 000

Abstract: Context. Circumstellar disks and outflows play a fundamental role in star formation. Infrared spectro-interferometry allows the inner accretion-ejection region to be resolved. Aims. We study the disk and Brγ-emitting region of MWC 297 with high spatial and spectral resolution and compare our observations with disk-wind models. Methods. We measured interferometric visibilities, wavelength-differential phases, and closure phases of MWC 297 with a spectral resolution of 12 000. To interpret our MWC 297 observatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(141 citation statements)
references
References 46 publications
10
127
4
Order By: Relevance
“…The model we developed for the more luminous and massive Herbig Ae/Be stars was described in detail in Grinin & Tambovtseva (2011) and Weigelt et al (2011). In the present paper, we briefly summarize the main properties of the model and the calculation method.…”
Section: Disk Wind Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The model we developed for the more luminous and massive Herbig Ae/Be stars was described in detail in Grinin & Tambovtseva (2011) and Weigelt et al (2011). In the present paper, we briefly summarize the main properties of the model and the calculation method.…”
Section: Disk Wind Modelmentioning
confidence: 99%
“…Several teams have modeled the hydrogen line profiles or interferometric observables of T Tauri stars (TTSs) or Herbig Ae/Be stars (HAEBEs) (e.g., Muzerolle et al 2001;Kurosawa et al 2006Kurosawa et al , 2011Lima et al 2010;Proga et al 1998;Tambovtseva et al 2001;Muzerolle et al 2004;RousseletPerraut et al 2010;Weigelt et al 2011;Lumsden et al 2012). It is difficult to investigate the structure of the emitting region in hot young stars because this region usually consists of several components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficiently high-resolution dispersion, such as the R ∼ 12,000 available with the VLTI AMBER instrument (Petrov et al 2007), make it possible to examine spectral line profiles in a spatially resolved or even imaged sense. AMBER has already been used for spectro-interferometric observations of the Herbig Be star MWC 297 as this high spectral resolution (Weigelt et al 2011). …”
Section: Spectroscopy and Spectro-interferometrymentioning
confidence: 99%
“…They showed that, for this object, the Brγ emission was coming from a region larger than the dusty-disk inner rim and that it was expanding, ruling out the possibility of an emission coming from an inner gaseous disk. This object was observed again by Weigelt et al (2011) with a higher spectral resolution and they managed to fully model their observations with a disk-wind model. For an other object, HD 104237, Tatulli et al (2007) found that the extension of the gaseous emission was of the order of the dusty disk inner rim.…”
Section: The Formation Of Massive Starsmentioning
confidence: 99%